Struktur Penyajian Barzanji pada Acara Aqiqah di Kenagarian Batu Hampa Kecamatan Koto XI Tarusan, Pesisir Selatan - Salsa Bila Nakiah; Syeilendra Syeilendra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to examine the structure of the presentation of Barzanji at the Aqiqah event in Batu Hampa, Koto XI Tarusan District, South Coast, with a focus on the regilius elements and local culture integrated in this ritual. Using a qualitative approach with a descriptive method, data were collected through direct observation, in-depth interviews with artists, religious leaders, and local communities, as well as visual documentation of the Aqiqah event. The results of the study show that the structure of presenting Barzanji consists of five main stages: preparation, opening, reading of the Barzanji text, joint prayer, and closing. The preparation stage involves arranging the venue and inviting religious leaders and the surrounding community. The reading of the barzanji text is carried out alternately by the artists. The joint prayer, led by Ustaz, became the core of the event with the aim of asking for blessings for the newborn. The event ended with a meal together as a symbol of gratitude and togetherness. The reading of Barzanji in the context of Aqiqah not only functions as a religious ritual, but also strengthens social and cultural relations in the community, and as a religious ritual this event is also a means of educating Islamic values for the younger generation and strengthening social ties in the community. This research provides new insights into the importance of preserving the Barzanji tradition in West Sumatra which is rich in regilian and cultural values.